The eubiotic perspective on utilization of tannins in phytotherapy and nutrition of pigs - Kostenko, Yuliia; Vlasova, Inna; Równicki, Marcin; Krüsselmann, Philip; Vahjen, Wilfried; Zentek, Jürgen; Tymoszewska, Aleksandra; Piwowarski, Jakub P. (Frontiers in Pharmacology, 2025)
Gastrointestinal eubiosis is essential for maintaining overall host wellbeing. Post-weaning diarrhea (PWD) is a common issue in pig development, arising from weaning stress, which disrupts the gut microbiota balance and increases susceptibility to infections. The primary bacterial pathogen linked to PWD is enterotoxigenic Escherichia coli (ETEC). While antibiotics have traditionally been used for prevention and treatment of ETEC infections, their use is declining due to the emergence of multidrug-resistant pathogens and restrictions on the use of growth-promoting antimicrobials. Consequently, eubiotics are increasingly valued in pig nutrition as a safer alternative to antibiotics. While prebiotics and probiotics are well-studied, phytochemicals like tannins, despite the long history of their traditional use in ethnoveterinary medicine, remain largely unexplored. This review explores the eubiotic properties of tannins and their potential applications in swine nutrition and phytotherapy. In vitro and in vivo studies demonstrate that tannin-rich plant materials positively influence intestinal microbiota and epithelium, resulting in enhanced nutrient absorption, growth performance, and overall health in pigs. Moreover, they indicate that tannins possess antioxidant, anti-inflammatory, immunomodulatory, and antiparasitic properties which can be beneficial in pig farming. This review also highlights the safety of tannin supplementation, along with its environmental and economic advantages. Furthermore, it discusses potential strategies to mitigate tannin toxicity. Finally, it points out the existing research gaps and suggests directions for further research. In summary, it presents tannins as promising eubiotic agents for improving gut health and combating PWD.